2016
DOI: 10.3389/fmicb.2015.01548
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Loop-Mediated Isothermal Amplification Assay for Serogroup Identification of Neisseria meningitidis in Cerebrospinal Fluid

Abstract: We have developed a novel Neisseria meningitidis serogroup-specific loop-mediated isothermal amplification (LAMP) assay for six of the most common meningococcal serogroups (A, B, C, W, X, and Y). The assay was evaluated using a set of 31 meningococcal LAMP assay positive cerebrospinal fluid (CSF) specimens from 1574 children with suspected meningitis identified in prospective surveillance between 1998 and 2002 in Vietnam, China, and Korea. Primer specificity was validated using 15 N. meningitidis strains (incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 34 publications
3
29
0
Order By: Relevance
“…The study of Bourke et al [18] was from the United Kingdom and had 141 nasopharyngeal swab samples and 144 blood samples. The study of Lee et al [19] was from South Korea and examined 31 cerebrospinal fluid samples. The study of Lee et al [20] was also from South Korea and examined 1574 cerebrospinal fluid samples (568 from Vietnam, 536 from China, and 470 from South Korea).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Bourke et al [18] was from the United Kingdom and had 141 nasopharyngeal swab samples and 144 blood samples. The study of Lee et al [19] was from South Korea and examined 31 cerebrospinal fluid samples. The study of Lee et al [20] was also from South Korea and examined 1574 cerebrospinal fluid samples (568 from Vietnam, 536 from China, and 470 from South Korea).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [19] 2015 South Korea 568 CSF PCR Lee et al [19] 2015 South Korea 536 CSF PCR Lee et al [19] 2015 South Korea 470 CSF PCR…”
Section: Blood Pcrmentioning
confidence: 99%
“…The study of Bourke et al [17] was from the United Kingdom and had 141 nasopharyngeal swab samples and 144 blood samples. The study of Lee et al [18] was from South Korea and examined 31 cerebrospinal fluid samples. The study of Lee et al [19] was also from South Korea and examined 1574 cerebrospinal fluid samples (568 from Vietnam, 536 from China, and 470 from South Korea).…”
Section: Discussionmentioning
confidence: 99%
“…The study of Higgins et al [21] was from Ireland and examined 65 blood samples. The study of Lee et al [18] used culturing as the reference standard, and all the other studies used PCR as the reference standard. Our meta-analysis results indicated that LAMP had an overall sensitivity of 94% (95% CI = 0.89 to 0.98) and an overall specificity of 100% (95% CI = 0.99 to 1.00) for the detection of N. meningitidis, and that the accuracy was high regardless of the sample type and geographic origin of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…These assays are therefore ideal for use as on or near point-of-care testing. Using this technology, LAMP-based methods have been used to detect Neisseria meningitis , Streptococcus pneumoniae , Haemophilus influenzae type b, M. tuberculosis as well as JEV in the CSF 6871 . The Xpert MTB/RIF assay has revolutionized the landscape of global tuberculosis control by providing an integrated and automated system that enables rapid clinical decision making in a POC or near-care context 67 .…”
Section: Molecular Methods In Diagnosis Of Cns Infectionsmentioning
confidence: 99%